Quality of Eucalyptus charcoal for use in silicon production - Ramos, Diêgo Correa (2018)
Replacing the use of fossil reductants with charcoal in silicon production has a great potential with respect to reducing CO 2 emissions, increasing silicon quality and yield. Nevertheless, charcoals can be produced from different raw materials and under various process conditions, and have different properties influencing further applications. This study aimed to evaluate the charcoal properties of three Eucalyptus spp. produced under different carbonization parameters for use in silicon production. In carbonization, the final temperature of carbonization (380 and 460 °C) and residence time (2 and 8 hours) were evaluated. A metallurgical coke was used for comparison purpose. Basic density, chemical composition and anatomy of wood were determined. Carbonizations in a laboratory kiln were done and the proximate and elemental analysis, porosity, apparent density, elemental composition, morphological characterization of pores and fibers, BET surface area, functional chemical groups and reactivity towards SiO gas of the charcoal were determined. The reactivity test was performed in an electric furnace with vertical reactor, at 1650 °C, in an inert atmosphere for 120 minutes. In the reactor, agglomerates made of a mixture of quartz (SiO 2 ) and silicon carbide (SiC) and charcoal sample were used. The results reveal that there is wood variability between the clones evaluated and strong correlations among wood and charcoal properties. The SiO reactivity test developed in this study was a useful tool to classify charcoal for silicon use. All charcoals had significantly higher SiO-reactivity than coke. The charcoal reactivity was influenced mainly by the apparent density and functional chemical groups on charcoal. Based on the parameters investigated and under the experimental conditions, the charcoal CL-3, the 380 °C final temperature of carbonization and the 8 h residence are most suitable to produce charcoal for use in silicon production process.